Histology Structure of Lymph and Uterus of White Rat (Rattus norvegicus) Given with Nanas Bongsai (Ananas comosus var. microstachys L.) - Fitmawati Fitmawati; Agus Saputra; Yohanes Yohanes; Hilwan Yuda Teruna; Dimas Pramita Nugraha; Yulis Hamidi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Nanas Bongsai (Ananas comosus var. microstachys L.) is an amazing herb which is used in traditional medicine by local people of Muara Lembu district as a potion to reduce pain while menstruation period for a women. The present work was designed to investigate its probable side effects on the histopathologic changes in limph and uterus tissues after treated with A. comosus var. microstachys L extract in female white rats. This is an experimental research consisted of five treatments and three repetitions. Treatment composed of two controls (P0 and P+) and given Nanas Bongsai extract with three different dosages. Histology result of lymph show that all treatments given with Nanas Bongsai with three different dosages have different diameter average of white pulp and there is no significant changes with normal control. While observation towards histology structure of endometrium thickness with dosage P1, dosage P2, dosage P3 is 206.333±33.486; 215.667±33.486; 197.667±60.871 respectively. The most thin endometrium layer found in treatment with dosage P3 compared to control P0. From this study showed that there is no toxic effect on uterus and lymph function of of Nanas Bonsai (A. comosus var. microstachys L.) at different doses, so the plant is secure for consumption by the community.